Estudos microbiológicos e de genética toxicológica de Handroanthus impetiginosus e sua potencial aplicabilidade a medicina veterinária - SILVA, Thaísla Andrielle da (2019)
Handroanthus impetiginosus Mattos has been used for a long time in traditional Medicine and several studies have shown the presence of chemical compounds with potential phytotherapeutic activity. Thus, the objective of this study was to evaluate the chemical composition (Gas Chromatography - MS) of the hydroalcoholic extract of H. impetiginosus (H.i.) peel, its antimicrobial potential against bacteria and yeasts (Broth Microdilution Test) and toxicity Micronucleus (MN) in bone marrow of mice, plasmid DNA Nicking, and Cytotoxicity in HaCat Cells). Thirty chemical compounds were identified by gas chromatography, H.i. showed antimicrobial activity against strains of bacteria and yeasts, with MIC (50 - 12.5 and 100 - 0.19 mg.mL-1, respectively). The MN assay suggested absence of genotoxicity, mild systemic toxicity, and antigenotoxic effects at the concentrations tested (0.5 - 2.0 g.mL-1). The HaCat cell test indicated dose-dependent cytotoxicity of H.i. from the concentration ≥1.56 mg.mL-1. In the genomic antioxidant assay, the concentrations (1,000 - 100 μg.mL-1) of H.i. partially protected the DNA from damage caused by the Fenton reaction, already in the genotoxic assay, H.i. was pro-oxidant at its highest concentration (5,000 µg.mL-1), however, at dosages (3,160 - 100 µg.mL-1) it did not cause any effect. These results indicate that H.i. (anti-bacterial and antifungal) and antigenotoxic activity, however, it is toxic in a dose-dependent manner for the cells evaluated, which justifies further studies in order to determine safer exposure conditions with applicability in animal health.